Motherhood, Career Aspirations, and Life Goals: Exploring Young Women’s Attitudes as a Factor in the Declining Fertility Rate in Sri Lanka - Michelle, Varuni; Bandara, Ruchira; Lakshman, Iresha (European Scientific Journal, ESJ, 2025)
The fertility rate in Sri Lanka has gradually declined over the last few decades. While existing literature has explored motherhood and career aspirations, few studies examine these dynamics among university students in Sri Lanka. This study aims to explore how young Sri Lankan female undergraduates perceive motherhood in relation to their career aspirations and life goals, offering a contextually grounded perspective in a Southern setting. The study adopted a mixed-method approach comprising a survey followed by in-depth interviews and focus group discussions. The sample comprised 300 female undergraduates from the Arts, Management, and Science faculties at the University of Colombo, including both first-year and final-year students. The study employed a pseudo-longitudinal design to compare differences in perceptions and attitudes toward motherhood across academic disciplines and stages of study. Findings indicate that the value placed on motherhood varies by discipline, with Arts and Management students generally prioritising it more than those in Science. Attitudes also shift between first-year and final-year students, as academic exposure and evolving career aspirations influence the timing and conditions under which motherhood is considered. Career goals, financial stability, and lifestyle preferences emerged as key factors shaping reproductive decisions, while concerns about balancing work and family persist across the sample. The study highlights the complex interplay between societal expectations, personal values, and professional ambitions in shaping young women’s reproductive choices in Sri Lanka. In conclusion, undergraduate perceptions of motherhood are shaped by disciplinary identity and socio-economic positioning, often leading to delayed motherhood due to anticipated role conflicts and financial constraints. Supportive policies, flexible work environments, and community-level interventions are essential to empower young women to navigate career and family while making informed reproductive choices.